2021
DOI: 10.3389/fchem.2020.599740
|View full text |Cite
|
Sign up to set email alerts
|

Design of DOX-GNRs-PNIPAM@PEG-PLA Micelle With Temperature and Light Dual-Function for Potent Melanoma Therapy

Abstract: Objective: The aim of this study was to construct light and temperature dual-sensitive micellar carriers loaded with doxorubicin (DOX) and gold nanorods (DOX-GNRs-PNIPAM@PEG-PLA, DAPP) for melanoma therapy.Methods: The DAPP self-assembled using fine-tuned physicochemical properties in water. The DAPP structure, temperature- and photo-sensitivity, drug-release, in-vitro serum stability, and cytotoxicity against melanoma B16F10 cells were evaluated in detail. The corresponding in-vitro and in-vivo therapeutic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Despite this size value not being within the size range normally considered optimal (100-200 nm), it is still within the range suitable for intravenous administration, circulation in the human body, and accumulation in the tumor tissue. [5,[35][36][37] The difference in TEM and DLS measurements can be attributed to the sample's physical state in each technique, dried preparation for TEM analysis commonly results in smaller nanoparticles sizes. [38] Additionally, the surface charge measurements showed that the Au-Alg-NHs have a negative value of −25 ± 4.5 mV, which is in accordance with the negative charge of Alg (Figure 2C).…”
Section: Synthesis and Characterization Of Au-alg-nhmentioning
confidence: 99%
“…Despite this size value not being within the size range normally considered optimal (100-200 nm), it is still within the range suitable for intravenous administration, circulation in the human body, and accumulation in the tumor tissue. [5,[35][36][37] The difference in TEM and DLS measurements can be attributed to the sample's physical state in each technique, dried preparation for TEM analysis commonly results in smaller nanoparticles sizes. [38] Additionally, the surface charge measurements showed that the Au-Alg-NHs have a negative value of −25 ± 4.5 mV, which is in accordance with the negative charge of Alg (Figure 2C).…”
Section: Synthesis and Characterization Of Au-alg-nhmentioning
confidence: 99%
“…Accordingly, systems such as, PNIPAM@ magnetic NPs (Fe 3 O 4 )/5-fluorouracil (5FU) and oxaliplatin (OXA)- acrylic acid (AA), 3-butenoic acid (3BA) or allylamine (AL) (pNIPAM@ Fe 3 O 4 /5FU/OXA-AA, 3BA, AL) [ 181 ], doxorubicin(DOX)-gold nanorods (GNRs)-PNIPAM@poly (d, l-lactide)-poly (ethylene glycol) (PLA-PEG) (DAPP)micelles (DOX-GNRs-PNIPAM@PEG-PLA,DAPP) [ 182 ], vancomycin (VANCO)/SF-Na Alg NPs/PNIPAM@epidermal growth factor (EGF) (VANCO/SF-Na Alg NPs/PNIPAM@EGF) [ 183 ], PNIPAM- superparamagnetic iron oxide nanoparticles (SPION)- etoposide (SPION-PNIPAM-Etoposide) [ 184 ], NaALG-g-P(NIPAM 80 - co -NtBAM 20 )/Dulbecco’s modified Eagle’s medium (DMEM) (NaALG-g-P(NIPAM 80 - co -NtBAM 20 )/DMEM) [ 185 ] and many more have been designed by researchers in order to intensify the use of PNIPAM polymer in the field of drug delivery [ 186 , 187 ]. Table 1 depicts the latest investigations of PNIPAM-based hydrogels in drug delivery.…”
Section: Pnipam-based Hydrogels In Drug Deliverymentioning
confidence: 99%
“…The micelle is susceptible to the influence of the in vivo environment like pH, temperature, or reduction–oxidation reactions, which may result in structural deformation and subsequent release of loaded drugs or induction of drug resistance. In accordance with this property, many pH-triggered and thermosensitive micelles have been designed to achieve targeted drug delivery ( Bae et al, 2005 ; Guo et al, 2018 ; Wang N. et al, 2020 ). Therefore, a micelle is more suitable for topical administration or in combination with other polymer materials when controlled drug release is desired ( Wen et al, 2017 ; Chen et al, 2019 ).…”
Section: Nanoparticlesmentioning
confidence: 99%